Great powers, small wars asymmetric conflict since 1945 - Deriglazova, L. V. (Larisa Valerʹevna) (Johns Hopkins University Press, 2014)
Presents a combination of quantitative research and two in-depth case studies. This book surveys armed conflicts post World War II in which one power is much stronger than the other. It focuses on the experiences of British decolonization after World War II and the United States in the 2003 Iraq war.